Growth and biochemical content of Arthrospira platensis cultured using Fresh Palm Oil Mill Effluent supplemented medium - Sukumaran, Puganeswary (2017)
Arthrospira, which is widely known as Spirulina, has gained growing commercial interest due to its attractive high-value biomass as an alternative and potential feedstock for food, feed, pharmaceuticals, nutraceuticals, cosmetics and so on. Numerous investigations are being conducted to optimize biomass of this microalga while reducing the production cost. Previously, studies have been done in the formulation of the cost-effective medium using wastewater. However, due to ethical reason, waste from human and animal is not suitable for microalgal cultivation intended for human consumption. Therefore, the present study was conducted to investigate the prospects of fresh palm oil mill effluent (fPOME) as an alternative and inexpensive growth medium in Arthrospira platensis cultivation. fPOME is non-toxic, golden-brown industrial wastewater generated as a by-product during crude palm oil extraction. The objective of this study is to determine the growth and biochemical content of A. platensis in fPOME supplemented medium under real environment. Accordingly, A. platensis was cultured in different concentrations of fPOME supplemented medium of 10 L (0%, 1%, 2%, 3% and 4% v/v) under outdoor conditions to find the optimum fPOME concentration for good growth, productivity and biochemical content of this microalga as in the control (modified Kosaric medium, MKM). Next, the biochemical content of A. platensis cultured using the optimum fPOME supplemented medium in scaled-up outdoor conditions (100 L) was compared with commercial Spirulina products. A. platensis cultured in T2 (1% v/v fPOME) reached significantly higher (p < 0.05) specific growth rate (0.277 μ d-1) and productivity (0.159 g L-1 d-1) compared to control and other treatments. A. platensis in T2 also showed high protein (50.23% dry weight), lipid (10.37% dry weight), total chlorophyll (1.05% dry weight), carotenoids (0.56% dry weight) and phycocyanin (10.93% dry weight), which were slightly comparable with control and significantly higher (p < 0.05) compared to other treatments. Under scaled up outdoor conditions, A. platensis cultured in 1% (v/v) fPOME supplemented medium attained significantly higher (p < 0.05) protein (56.90% dry weight), lipid (12.63% dry weight), phycocyanin (15.95% dry weight), carotenoids (0.58% dry weight), total phenolic (5.70 mg Gallic acid equivalent per gramdry weight) content and second highest total chlorophyll content (1.20% dry weight) compared to other commercial Spirulina products. Besides, the preparation of 1,000 L of fPOME supplemented medium would cost about RM 13.52, in which, 98% and 42% of the medium cost can be saved compared to the generally used standard Kosaric medium (SKM) and MKM respectively. These findings showed the potential of fPOME as a suitableg rowth medium in cost-effective Arthrospira cultivation under natural conditions without adversely affecting the algal growth and biochemical content. Meanwhile, this study also added value to this wastewater as a cheaper and readily available fertilizer in microalgal biomass production. Moreover, it is also proven that the commercial cultivation of Spirulina at low cost is feasible in Malaysia with proper cultivation approach